Inovasi Pelayanan Publik Melalui Program Aplikasi Go PPU di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Penajam Paser Utara - Shelly Noorlisa; Muhammad Hairul Saleh; Anwar Alaydrus (Jurnal Ilmu Pemerintahan, 2022)
This study aims to analyze and describe the online application-based GO PPU innovation carried out by the North Penajam Paser Regency Disdukcapil and to find out that the GO PPU application program can change people's mindset towards public services at Disdukcapil North Penajam Paser Regency. The research was conducted at the Department of Population and Civil Registration of North Penajam Paser Regency. The type of research using descriptive qualitative. Data collection was carried out by means of library and field research using observation, interview and documentation methods. The results of the study show that Public Service Innovation through the GO PPU Application program at the Population and Civil Registration Office of North Penajam Paser Regency is something that is innovative for the community using the GO PPU application, based on the relative advantages of GO PPU compared to previous services which can be seen in terms of time faster and can be done at home, for compatibility GO PPU is in accordance with applicable service standards, for complexity GO PPU is easy to operate and service procedures make it easier for the community, GO PPU goes through a trial phase, GO PPU is introduced through outreach and GO PPU is easy to observe for community and easily accessible. While the GO PPU application has not completely changed the people's mindset to make the most of the GO PPU application so that there is no need to come directly to Dukcapil to take care of population administration, however, it cannot be denied that there are still people who do not know about GO PPU